The Role of Strategic Leadership in Enhancing Institutional Performance in Commercial Banks in the West Bank - Sweiss, Mohammad; qubbaj, ihab (The Arab Journal of Administration, 2021)
The aim of this study is to identify the reality of applying strategic leadership practices, to examine the ability of commercial banks in the West Bank in achieving institutional performance, and to identify the nature of the relationship to strategic leadership practices that represented by (strategic orientation, organizational culture, human capital, ethical practices) in achieving Institutional performance . In addition to test the change in the dependent variable (institutional performance) as a result of the change in strategic leadership practices. This was tested by the study hypotheses. The study tool was prepared and distributed to the sample of (114) commercial banks operating in the West Bank. This study reported several results: the percentage of performance of strategic leadership practices was high (73.211%), while the field of institutional performance achieved (76.564%). The results also reported a high (68.50%) positive correlation between strategic leadership practices and institutional performance. There were statistically significant differences at the level of (a≤0.05)between strategic leadership and institutional performance in commercial banks operating in the West Bank due to variables (gender, age, number of years of service), on the other hand, the results showed that there are no differences in strategic leadership and performance according to the academic qualifications and the level of career.